THE HISTORICAL DEVELOPMENT OF THE STUDY OF BROCA'S APHASIA - Lian Lau, Yoke; Kim Loi, Chek; Nor Azan bin Abdullah, Mohd (MNJ (Malang Neurology Journal), 2021)
Broca's aphasia is a type of aphasia named after the French surgeon Broca. Broca's aphasic patients experienced difficulty in speaking, but they could understand both spoken and written language. There were three essential patients in the historical development of the study of Broca's aphasia. Louis Victor Leborgne (1809–1861) was also known as Monsieur Leborgne or 'Tan' as he could only utter the syllable 'Tan' throughout his 21 years of illness. The second patient was called Lazare Lelong. His language ability was slightly better than Leborgne. He could utter simple syllables, such as oui (yes), non (no), and this (trois or three). The third patient was Gage, a railway company worker. Broca studied similar cases in the following years and planned a brain function localization theory.